Analysis of gene expression profiles reveals the regulatory network of cold‐inducible RNA‐binding protein mediating the growth of BHK‐21 cells. (12th March 2015) - Tang, Cheng; Wang, Yuanwei; Lan, Daoliang; Feng, Xiaohui; Zhu, Xin; Nie, Peiting; Yue, Hua
Abstract Cold‐inducible RNA‐binding protein (Cirp), the first cold‐shock protein identified in mammals, is a sensor protein whose expression increases in response to stress. Recent reports have shown that Cirp is involved in cell proliferation, development, circadian modulation under physiological conditions, and tumor formation and progression. However, the molecular mechanisms underlying the activities of Cirp in the mammalian kidney cells remain unclear. In this study, we constructed BHK‐21cells overexpressing Cirp (Cirp + BHK‐21) knockdown BHK‐21 cells (Cirp − BHK‐21) to investigate the function of Cirp in cell proliferation. We analyzed the gene expression of Cirp − BHK‐21 cells using genome‐wide expression microarrays to explore the molecular mechanism of Cirp action. We found that (1) Cirp overexpression significantly enhanced cell proliferation, whereas Cirp knockdown dramatically reduced cell proliferation, suggesting that Cirp is a positive regulator of BHK‐21 cell proliferation. (2) Differentially expressed genes in Cirp − BHK‐21 and control cells were shown to be involved in many biological processes. (3) Pathway analysis showed that five enriched pathways, namely, Focal adhesion, Mapk, Wnt, Apoptosis, and Cancer‐related signaling pathways, were identified as central pathway networks regulated by Cirp. These results can provide new insights into the molecular mechanisms of Cirp function.